دراسة الخصائص البصرية لأغشية اكاسيد النحاس المحضرة بطريقة الترسيب بواسطة الليزر - سلام هبة; فاضل مسلم (Al-Nahrain Journal of Science, 2018)
In this work, thin films of CuO, Cu2O were deposited on glass substrates using pulse laser deposition technique. The Structure Characterization of the film was carried out with XRD. The results of XRD show that all samples have a polycrystalline structure, The optical measurements on the deposited films were performed to determine the transmission spectrum and the absorption coefficient as a function of incident wavelength. Then from the optical parameters, extinction coefficient, value and type of energy gap, type of the dominant absorption processes, refractive index as functions of incident photon energy, were determined. The Energy gap is found to be equal to 2 eV for Cu2O and 1.7 eV for CuO that is direct transfer